2021
DOI: 10.1186/s12909-021-03003-0
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of external academic accreditation of undergraduate medical program on students’ satisfaction

Abstract: Background The external academic accreditation is a quality assurance and auditing process that focuses on the structure, process, and outcome of the education. It is an interrupting and highly demanding process in terms of effort, time, financial, and human resources. However, it is unclear in the literature how much of these external quality assurance practices impeded in the accreditation processes would reflect on the other end of the learning pathway, including student satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…We chose to analyze domains considered important to the needs of Brazilian society and also the international literature (social accountability, integration with the health system, faculty development policies and environmental sustainability) [ 2 , 9 , 16 ]. We also presented detailed description of student’s domains, that we consider one of the stronger aspects of SAEME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to analyze domains considered important to the needs of Brazilian society and also the international literature (social accountability, integration with the health system, faculty development policies and environmental sustainability) [ 2 , 9 , 16 ]. We also presented detailed description of student’s domains, that we consider one of the stronger aspects of SAEME.…”
Section: Discussionmentioning
confidence: 99%
“…Medical schools must promote a healthy educational environment that is positive for learning and personal development [ 2 , 21 ]. This objective has been partially achieved by medical schools (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could promote systematic mapping of the curriculum and assessment strategies (Blouin et al, 2018). Assessing scaled students' satisfaction as an indirect measure of accreditation impact on medical programme in Saudi Arabia, Al-Eyadhy and Alenezi (2021) found that it has a positive impact on course conduction and practical/clinical experience. At the course level, another example is that the mission and objectives of the institution were incorporated into the course design (Hou et al, 2015).…”
Section: External Quality Assessment: Reported Positive Changesmentioning
confidence: 99%
“…Emotional and social aspects are vital to the development and maintenance of interpersonal relations, including those between healthcare providers and patients 1 . The emotional reactions of university students are reflected by their academic satisfaction 2 . Students’ satisfaction with their undergraduate course may involve factors such as academic performance 4 , 5 , motivation in the choice of course 4 and job prospects 6 .…”
Section: Introductionmentioning
confidence: 99%